ANALYSIS OF VACANT LAND VALUE DETERMINANTS IN URBAN ZARIA, NIGERIA - Abbas, S. (FUDMA Journal of Sciences, 2023)
The study tried to analyse the determinants of vacant land values in urban Zaria Nigeria. This is in realization of the fact that though several studies have been carried out on land values in Nigeria, studies on vacant land values are hard to come by. Again, most of the previous studies used data obtained from occupants of developed properties, while this study utilised questionnaire survey, administered on estate agents/dealers, identified through snowball sampling. The analytical tool was multiple regression analysis, where vacant land value was the dependent variable while the several explanatory variables, identified from literature, estate agents and the authors’ knowledge of the local area, were the independent variables. The results shows that the major determinants of vacant land values in the area include neighbourhood quality, road quality, development potential, and ethnic composition, with p values of 0.012, 0.024 and 0.035 respectively. In line with that the hypothesis put forward was tested, and it shows that there is a significant relationship between vacant land values and many of the explanatory variables. This implies that variables like neighbourhood quality, quality of road, development potential, ethnic composition, proximity to high institutions, distance from sub-centre, distance from CBD, and water supply, in that order, all help to account for vacant land value variations in urban Zaria. It was, therefore, recommended that these factors should be given due consideration in planning and policy formulation for future development of the area.